Indonesian Language Learning at MI Najil Ummah, What Form of Spoken Discourse Formed? - Abdul Ghoni Asror (Jurnal Pendidikan Edutama, 2024)
This study aims to describe the structure of spoken discourse used by teachers and students of Grade 4 MI Najil Ummah Kenep in the learning process in class. The research was carried out at MI Najil Ummah with a total of 9 students as research objects. This study uses a qualitative method that is descriptive. Data is obtained through oral discourse that is used by teachers and students during the learning process in class. The results in this study are (1) learning uses polylogic discourse more often, namely communication is carried out by more than two people with students being more active in learning guided by the teacher in class, (2) sentences in spoken discourse that are used tend to be less structured but can be understood properly. well, (3) learning uses descriptive discourse, namely the teacher can explain the material in detail and according to the students' daily situations.